Constitutional approach in studying human diseases at the present stage - N. Yu. Klimov; Y. Yu. Vinnik; A. V. Andreychikov; A. S. Maximov (Сеченовский вестник, 2018)
The study of the relationship between somatotypological features of a person and the course of diseases is today an important stage in the development of medical science. The somatotype is genetically determined and is a constant objective characteristic of a person from birth to death. Age changes, illnesses, increased physical activity change the size and shape of the body, but not the somatotype. To date, considerable theoretical and clinical material has been accumulated, which conﬁrms the important role of the somatotype in the emergence and development of pathological processes in the human body. In the literature there are data on somatotypological features of the course of diseases of the respiratory system, cardiovascular and nervous systems, and the gastrointestinal tract. At the same time, when analyzing the literature data, we did not ﬁnd any work on the eﬀect of the somatotype on the course of benign hyperplasia andprostate cancer. The identiﬁcation of these patterns will be a valuable contribution to the early diagnosis of the above listed diseases.